Teaching modern computer science topics in foreign experiences (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
This article explores a novel approach to teaching modern computer science topics through foreign experiences. In an era of globalization, it is imperative for educators to embrace diverse perspectives and provide students with a comprehensive understanding of computer science within a global context. This paper discusses the implementation of foreign experiences as a pedagogical tool, emphasizing its impact on student engagement, cultural awareness, and skill development. Through a comprehensive analysis of existing literature, the article highlights the potential benefits and challenges associated with this teaching methodology